STRUKTUR, ESTETIKA, DAN PERUBAHAN KONTEKS DALAM WACANA PIDATO UPACARA PERKAWINAN MASYARAKAT JAWA - Mulyana Mulyana (LITERA, 2011)
This study aims to describe language use in a wedding ceremony in terms of linguistic elements making a speech discourse possess Javanese literary esthetics and expressions of contexts and changes occurring in wedding ceremonies conducted by Javanese people. This study employed a sociolinguistic approach involving discourse analysis. It used data obtained from wedding ceremony speeches. The speeches were documented directly from Javanese wedding ceremonies in the area of Yogyakarta. The results of the data analysis are as follows. First, the spoken languages in Javanese wedding ceremonies include Javanese, Indonesian, and a mixed language called Jawindo (Jawa-Indonesia). Second, there are a variety of esthetic elements employed in wedding speech discourse. Third, changes in wedding speech discourse result from the underlying contexts.